To See the Earth before the End of the Antiblack World. Issue 2 (16th May 2022) - Howard, Jonathan
Abstract : This essay takes up the fundamental tension in black study between black life and black death, and forwards the idea of black ambivalence as a way of theorizing this tension. But given recent conceptions of the scope of black death as total and constitutive of what has generally come to be thought under the rubric of the "antiblack world, " this essay also asks what room is left for the thought of black life, not as a meager or even primarily defiant feat, but a veritable abundance. In the effort to actually think what Christina Sharpe has called "the largeness that is black life, " without flinching from the sense of antiblackness as indeed constitutive of a world, I propose a practice of black study that holds open a critical distinction between the world and what the poet Ed Roberson has alternatively called "the Earth." Ultimately, I argue that even if the world is totally defined by antiblackness, blackness is not totally defined by that world; and has further to be appreciated as a relationship to the Earth. It's when a sense of the larger Earth enters black study that we are able to appreciate black life as a veritable largeness.